Ynamide Carbopalladation: A Flexible Route to Mono‐, Bi‐ and Tricyclic Azacycles. Issue 36 (16th July 2015) - Campbell, Craig D.; Greenaway, Rebecca L.; Holton , Oliver T.; Walker, P. Ross; Chapman, Helen A.; Russell, C. Adam; Carr, Greg; Thomson, Amber L.; Anderson, Edward A.
Abstract Bromoenynamides represent precursors to a diversity of azacycles by a cascade sequence of carbopalladation followed by cross‐coupling/electrocyclization, or reduction processes. Full details of our investigations into intramolecular ynamide carbopalladation are disclosed, which include the first examples of carbopalladation/cross‐coupling reactions using potassium organotrifluoroborate salts; and an understanding of factors influencing the success of these processes, including ring size, and the nature of the coupling partner. Additional mechanistic observations are reported, such as the isolation of triene intermediates for electrocyclization. A variety of hetero‐Diels–Alder reactions using the product heterocycles are also described, which provide insight into Diels–Alder regioselectivity.